2011
DOI: 10.1007/s00535-011-0417-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in CTLA4 and SLC4A2 are differentially associated with the pathogenesis of primary biliary cirrhosis in Japanese patients

Abstract: CTLA4 and SLC4A2 genetic polymorphisms are differentially associated with PBC development and progression, as well as anti-gp210 or anti-centromere antibody production, in Japanese PBC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
(61 reference statements)
3
21
0
Order By: Relevance
“…Allelic variations in TNFa and solute carrier family 4 anion exchanger, member 2 (SLC4A2) but not CTLA4 have a significant impact on the progression of PBC [9]. However, the latter was not confirmed in a Japanese study, which reported association of CTLA4 SNPs with progression of the disease [50]. Our study is in agreement with other previous European [46] and Japanese studies [48].…”
Section: Discussionsupporting
confidence: 93%
“…Allelic variations in TNFa and solute carrier family 4 anion exchanger, member 2 (SLC4A2) but not CTLA4 have a significant impact on the progression of PBC [9]. However, the latter was not confirmed in a Japanese study, which reported association of CTLA4 SNPs with progression of the disease [50]. Our study is in agreement with other previous European [46] and Japanese studies [48].…”
Section: Discussionsupporting
confidence: 93%
“…In follow-up studies of GWAS datasets, associations of STAT4 variation with ANA status and CTLA4 variants with anti-centromere and gp210 have been identified in Japanese PBC patients [104] and TNFSF15 polymorphisms have been linked to functional changes in the gene product. Differences in mRNA and protein expression were also seen in both PBC and healthy subjects carrying this variant, although a link to outcome or phenotype remains unclear [105].…”
Section: Relating Immunogenetic Observations To Clinical Phenotypesmentioning
confidence: 99%
“…Polymorphisms in the AE2 gene that reduce transporter expression have been linked to primary biliary cirrhosis due to decreased expression of this transporter (Aiba et al, 2011;Juran, Atkinson, Larson, Schlicht, & Lazaridis, 2009;Medina, 2011). AE2-deficient mice also develop primary biliary cirrhosis (Salas et al, 2008).…”
Section: Slc4 Family Of Anion Transportersmentioning
confidence: 99%